Assessment of the impact of aerosol from a potential modified risk tobacco product compared with cigarette smoke on human organotypic oral epithelial cultures under different exposure regimens. (May 2018) - Zanetti, Filippo; Sewer, Alain; Scotti, Elena; Titz, Bjoern; Schlage, Walter K.; Leroy, Patrice; Kondylis, Athanasios; Vuillaume, Gregory; Iskandar, Anita R.; Guedj, Emmanuel; Trivedi, Keyur; Schneider, Thomas; et al.
Abstract: Cigarette smoke (CS) is affecting considerably the oral mucosa. Heating, instead of burning, tobacco reduces consistently the amount of toxic compounds and may exert a lower impact on oral health than combusted cigarettes. The carbon-heated tobacco product 1.2 (CHTP1.2) is a potential modified risk tobacco product (MRTP) based on heat-not-burn technology. Using a systems toxicology assessment framework, we compared the effects of exposure to CHTP1.2 aerosol with those of CS from a reference cigarette (3R4F). Human organotypic cultures derived from buccal and gingival epithelia were exposed acutely (28-min) or repeatedly (28 min/day for 3 days), respectively, to two matching concentrations of CHTP1.2 aerosol or 3R4F CS, and a non-diluted (100%) CHTP1.2 aerosol. The results showed an absence of cytotoxicity, reduction in pathophysiological alterations, toxicological marker proteins, and inflammatory mediators following exposure to CHTP1.2 aerosol compared with 3R4F CS. Changes in mRNA and miRNA expression were linked by an integrative analysis approach, suggesting a regulatory role of miRNAs in several smoke/disease-relevant biological processes induced by 3R4F CS. The identification of mechanisms by which potential MRTPs can reduce the impact of tobacco use on biological systems is of great importance in understanding the molecular basis of the smoking harm reduction paradigm. Graphical abstract: Highlights: Aerosols of a heat-not-burn tobacco product elicited lower impact on oral organotypic cultures than cigarette smoke. Systems toxicology revealed changes at the molecular level not otherwise apparent from morphological features. miRNA/mRNA integrative analysis evidenced potential miRNAs contributing to cigarette smoke adverse effects on oral health.